P-T CONSTRAINTS FROM PHYLLOSILICATES OF THE LIGURIDE COMPLEX OF THE POLLINO AREA (SOUTHERN APENNINES, ITALY): GEOLOGICAL INFERENCES - Cavalcante, Francesco; Belviso, Claudia; Laurita, Salvatore; Prosser, Giacomo (Ofioliti, 2012)
In this paper a mineralogical study of pelite and metapelite samples collected in the Pollino area (Southern Apennines, Basilicata, Italy) was performed byX-ray diffraction (XRD), with the aim to define in detail the thermobaric conditions of the ophiolite-bearing Liguride Complex during subduction. The twomain tectonic units of the Liguride Complex, namely the metamorphic Frido Unit and the non-metamorphic North Calabria Unit, have been sampled in thisstudy. Results indicate that in the Pollino area the metamorphic grade show an overall decrease from the SW to the NE. The Frido Unit it is characterized byHP/LT metamorphism. The highest values of temperature (280-330°C) and pressure (11-13 kbar) were detected in the southern sector of the area. The intermediatevalues (T = 250±30°C and P = 8-10 kbar) were observed in the central sector, whereas lowest values (T = 180±20°C and P = 7±0.5 kbar) were registeredin the northern sector. These thermobaric conditions and the inferred geothermal gradient (≈ 8°C/km) are in accordance with the lawsonite-blueschistmineral assemblage shown in associated metabasite and with the presence of aragonite in the carbonate levels. Data obtained from pelites of the North-CalabriaUnit indicate high diagenetic thermobaric conditions with temperatures of 110-150°C and pressures of 2-3 kbar. More in detail, temperature values of130-150°C and of 110-140°C are obtained in the Crete Nere and the Saraceno Formations, respectively. These moderate variations in the diagenetic grademight be influenced by differences in the bulk rock composition. The wide range of temperature and pressure conditions documented within the LigurideComplex indicates that samples have been collected in different thrust sheets characterized by variable metamorphic overprint. Systematic variations in thermobaricconditions are particularly evident within the metamorphic Frido Unit, which is probably made up of some thrust sheets and/or slices derived fromdifferent portions of the accretionary wedge.